Five-Minute Apgar Score and the Risk of Mental Disorders During the First Four Decades of Life: A Nationwide Registry-Based Cohort Study in Denmark - He, Hua; Yu, Yongfu; Wang, Hui; Obel, Carsten Lyng; Li, Fei; Li, Jiong (Frontiers in Medicine, 2022)
Objectives: The associations of long-term risks of full spectrum of mental disorders with clinically reassuring but suboptimal score range 7-9 remain unclear. This study investigated these associations during up to 38 years of follow-up. Methods: In a nationwide cohort study of 2213822 singletons born in Denmark during 1978-2015, we used cox regression to estimate hazard ratio (HR) of mental disorders with 95% confidence interval (CI). Results: A total of 300679 (13.6%) individuals were diagnosed with mental disorders. The associations between suboptimal Apgar scores 7-9 and mental disorders differed by attained age. In childhood (≤18 years), declining Apgar scores were associated with increased risks of overall mental disorders with HRs (95% CI) of 1.13(1.11-1.15), 1.34(1.27-1.41), 1.48(1.31-1.67) for Apgar scores of 7-9, 4-6, and 1-3, respectively, compared with a score of 10. A dose-response association was seen even within the score range from 9 to 7 (HR 1.11[95% CI: 1.08-1.13], 1.14[1.10-1.18] and 1.20[1.14-1.27], respectively). Of note, individuals with scores of 7-9 had increased risks of organic disorders (HR: 1.27, 95% CI: 1.05-1.53), neurotic disorders (HR: 1.07, 95% CI: 1.03-1.11) and a wide range of neurodevelopmental disorders, such as intellectual disability (1.87, 1.76-1.98), childhood autism (1.13, 1.05-1.22) and attention deficit hyperactivity disorder (1.10, 1.06-1.15). In early adulthood (19~39 years), suboptimal Apgar scores 7 to 9 was not associated with the risks of overall and specific mental disorders. Conclusion: Infants born with clinically reassuring but suboptimal 5-minute scores 7 to 9 are at increased risks of a wide spectrum of mental disorders in childhood.